1989
DOI: 10.1007/bf00314500
|View full text |Cite
|
Sign up to set email alerts
|

Is Parkinson's disease of early onset a separate disease entity?

Abstract: Two groups of patients suffering from Parkinson's disease were studied. The first group consisted of 23 patients with an onset age before 40 years; in the second group of 21 patients the onset was after age 50. The clinical findings and the course of the disease were very similar in each group. In spite of a longer disease duration in the patients with early onset of the disease there was no difference in motor impairment; the younger patients did better in mental testing and they were taking less dopaminergic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Our results are in agreement with these studies, which consistently identified a cohort of PD patients with young onset of disease. [34][35][36] This subgroup demonstrates a slower rate of disease progression, 5 29 37 38 less cognitive impairment, 29 38 39 and a greater potential to develop motor fluctuations 4 17 (possibly as a consequence of the prolonged exposure to L-dopa) compared with subgroups with later disease onset, as also shown with our cluster analysis solution.…”
Section: Discussionsupporting
confidence: 72%
“…Our results are in agreement with these studies, which consistently identified a cohort of PD patients with young onset of disease. [34][35][36] This subgroup demonstrates a slower rate of disease progression, 5 29 37 38 less cognitive impairment, 29 38 39 and a greater potential to develop motor fluctuations 4 17 (possibly as a consequence of the prolonged exposure to L-dopa) compared with subgroups with later disease onset, as also shown with our cluster analysis solution.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies on the relevance of this factor have produced controversial results. Some found no differences in the prevalence of dyskinesias between patients with earlier or with older onset patients with Parkinson's disease [5,7,15], whereas others report that early-onset patients develop earlier and more frequently dyskinesias than those with late onset [6,8,10,14,22]. Differences may be explained in part by methodological factors related to sample's size or the confounding effect of other variables such as levodopa dose or duration of levodopa treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these papers have included juvenile-onset PD. It is possible that cases of PD in patients under 40 years of age may reflect environmental and genetic factors in the disease etiology [3]. Although patients with PD are mostly of advanced age [4,5], few papers have described the clinical features of PD occurring in patients up to middle age.…”
Section: Introductionmentioning
confidence: 99%